Are hearing aid owners able to identify and self-report handling difficulties? A pilot study. (2nd November 2017) - Bennett, Rebecca J.; Meyer, Carly; Olaithe, Michelle; Schmulian, Dunay; Eikelboom, Robert H.
Abstract: Objective : Although clinician administered surveys evaluating hearing aid handling skills exist, the development of a self-administered version may reduce clinical load, save consultation time, and facilitate more frequent use than face-to-face consultations allow. However, there is currently no evidence to support whether hearing aid owners can accurately self-report hearing aid handling skills via self-report survey that systematically evaluates the ability to accurately perform the individual aspects of hearing aid handling required for effective hearing aid management. Design : An explorative pilot study using a prospective research design. Study sample : Nineteen adult hearing aid owners, aged between 65 and 93 years. Results : The self-administered survey demonstrated high sensitivity when compared with clinician evaluation of skills, with 93% of participants accurately self-identifying and reporting whether hearing aid handling skill training was required. Conclusions : Hearing aid owners are able to accurately self-report hearing aid handling difficulties when provided with an itemised list of skills.